Ethiopia Country Environmental Analysis : Realizing Green Transformation - World Bank (World Bank, Washington, DC, 2020)
The CEA assesses the country’s key environmental challenges in this transformation process and the capacity to manage them. It takes a holistic perspective on environmental issues, covering the major sectors of the economy. The CEA focuses on four clusters of sectors that, together, are determining Ethiopia’s development path: (i) resilient rural landscapes, (ii) green industrialization, (iii) sustainable urbanization, transport and living conditions, and (iv) sustainable energy access. Achieving Ethiopia’s CRGE goals requires shifting the trajectory that each cluster is on toward more sustainable options. For each of these clusters, the CEA discusses their current and intended trajectories (environmental trends such as degradation and pollution, and the government plans and strategies to respond to these trends) as well as the policies, incentives, institutions, information (the upstream enabling environment) needed to put the country on a green, clean, and resilient development pathway. The report also highlights practical experiences from Ethiopia and elsewhere. The bulk of the analysis in the CEA focuses on key challenges in the enabling environment in terms of policies, institutions, incentives, and information—which can contribute to success in achieving sustainability and mobilizing investment if well-designed and consistently implemented, and can impede success if not.